Bounding quantum dark forces - Brax, Philippe; Fichet, Sylvain [UNESP]; Pignol, Guillaume (American Physical Society (APS), 2018)
Dark sectors lying beyond the Standard Model and containing sub-GeV particles which are bilinearly coupled to nucleons would induce quantum forces of the Casimir-Polder type in ordinary matter. Such new forces can be tested by a variety of experiments over many orders of magnitude. We provide a generic interpretation of these experimental searches and apply it to a sample of forces from dark scalars behaving as 1/r3, 1/r5, 1/r7 at short range. The landscape of constraints on such quantum forces differs from the one of modified gravity with Yukawa interactions and features, in particular, strong short-distance bounds from molecular spectroscopy and neutron scattering.